Pengembangan dan Pelatihan Sistem Pengukuran Antropometri Digital kepada Kader Posyandu sebagai Upaya Peningkatan Pelayanan Posyandu Balita dan Pencegahan Dini Stunting - Sentagi Sesotya Utami; Aji Nurohman; Jujun Mulyana; Tiara Kus Anindita Maharani; Nadine Mutiara Wibowo; Jeihan Vitriashiila Maharani; Izzah Marisa Tasallia; Annisa Maulidina; Salsabila Aulia Rahmadani (Jurnal Pengabdian, Riset, Kreativitas, Inovasi, dan Teknologi Tepat Guna, 2024)
The growth and development of toddlers reflects the health of future generations. To prevent stunting, the integrated health service post (posyandu) plays a crucial role in regularly monitoring child growth. The Ministry of Health has endeavored to implement digital anthropometric tools in posyandu centers. However, in practice, many community health workers still rely on manual recording due to challenges in utilizing the government's digital anthropometry tools. This digital anthropometric system is designed to offer a more accurate solution for measuring toddler growth. Unlike existing digital anthropometry tools, this system is also integrated with an intuitive application to facilitate measurements by community health workers. Beyond measurement functions, this digital anthropometric system includes a health dashboard that provides a comprehensive view of toddler growth status and automatically generates analytical graphs. Consequently, healthcare providers can swiftly identify potential stunting cases and take early actions. This community engagement initiative aims to develop and to train the usage of digital anthropometric measurement systems for posyandu workers in Karangsari and Sarwodadi Villages. The approach involves training through Focus Group Discussions (FGDs) for posyandu workers. Subsequently, the evaluation of the digital anthropometric system's usage employs the System Usability Scale (SUS), employing ten statements as benchmarks for its utilization. From the System Usability Scale (SUS) evaluation results, an overall score of 56.58 was obtained, indicating an "OK" level of usability. This outcome demonstrates that the digital anthropometric system is functional, yet posyandu workers still require guidance from experienced midwives already familiarized with the system's operation.